2018
DOI: 10.1093/scipol/scy044
|View full text |Cite
|
Sign up to set email alerts
|

Policies and patenting to stimulate the biotechnology sector: Evidence from The Netherlands

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Existing research on the relationship between technology and institutions increasingly focuses on the effects of institutions on technology [15,16,18,22]. The effects are mainly reflected in the following aspects.…”
Section: Biotechnology and Institutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research on the relationship between technology and institutions increasingly focuses on the effects of institutions on technology [15,16,18,22]. The effects are mainly reflected in the following aspects.…”
Section: Biotechnology and Institutionsmentioning
confidence: 99%
“…The effects are mainly reflected in the following aspects. First, institutions stimulate and promote the research and development (R&D) of technology, and most countries in the world have put forward policies to support R&D activity [15,23]. Bronzini and Piselli [16] studied the impact of an R&D subsidy program on firm innovation, and found that the program had a significant impact on the number of patent applications.…”
Section: Biotechnology and Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioenergy and biofuels industry received the highest degree of R&D funding and good support for experimental and demonstration plants at the industrial production phase (e.g., via quotas, green electricity regulations, and tax incentives). This approach contributes to industry distortions about the supply and cost of feedstock, which in turn disadvantages biomaterials and bioplastics [5,79]. When these benefits and aids make oil markets more appealing, bio-refineries are overwhelmingly energy-oriented.…”
Section: Alternative Uses For Feedstockmentioning
confidence: 99%
“…In certain regions and countries, it is possible to support the production, optimize land use, and emphasize a sustainable green raw material culture to the bio-based economy of alternative crop systems (e.g., perennial crop formation and short rotation coppices under-utilized soils). A recent study in the US [81] shows that land management practices allow the on-going growth of herbaceous perennial species on marginal soils, non-sturdy yet harvesting fertilization, do not include the release into our environment of high levels of carbon dioxide [79].…”
Section: Alternative Cropping Systemsmentioning
confidence: 99%